A note on the devising of superconvergent HDG methods for Stokes flow by M-decompositions. (29th June 2016) - Cockburn, Bernardo; Fu, Guosheng; Qiu, Weifeng
Abstract : In this article, we to devise superconvergent hybridizable discontinuous Galerkin methods on unstructured polygonal/polyhedral meshes for the Stokes equations of incompressible fluid flow by using $M$ -decompositions. We do this for two formulations of the equations, namely, for the velocity gradient–velocity-pressure formulation, and for the more difficult strain rate–velocity-pressure formulation. We also show how to locally postprocess the approximate velocity to obtain a globally divergence-free and $H(div)$ -conforming velocity converging faster than the original approximate velocity.